CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE, INSTITUTIONAL OWNERSHIP, AND ASSET GROWTH TO IMPROVE FIRM VALUE - Yahya, Adibah; Triwibowo, Edi; Sari, Arum Kartika; Kartika, Dewi (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2024)
Firm value is investors' perception of the company's success in managing its resources which is reflected in the share price. Several factors that influence company value include the company's ability to carry out social responsibility which is related to the public value of the company. Apart from that, Good Corporate Governance can also influence the size of the company's value. However, internal factors, namely asset growth, can also have an impact on company value. This research aims to analyze the influence of Corporate Social Responsibility Disclosure, Institutional Ownership and Asset Growth on company value in companies listed on the Indonesia Stock Exchange. The sample companies are consumer goods companies with data analysis methods using descriptive and verification analysis. The results showed that partially Corporate Social Responsibility Disclosure had a negative and insignificant effect on firm value but Institutional Ownership and Asset Growth had a positive and significant effect on firm value.